Fire in the sky - Hunter, Erin. (New York : Harper, 2011)
Despite their misgivings about the many dangers that lie ahead, the bears venture out onto the Everlasting Ice and learn of their final destination with the help of a mystical bear spirit.
Reprint. Originally published: c2010.
770
Keywords: Bears -- Fiction; Fantasy fiction